1989
DOI: 10.1021/jm00131a009
|View full text |Cite
|
Sign up to set email alerts
|

Structural studies on bioactive compounds. 8. Synthesis, crystal structure and biological properties of a new series of 2,4-diamino-5-aryl-6-ethylpyrimidine dihydrofolate reductase inhibitors with in vivo activity against a methotrexate-resistant tumor cell line

Abstract: A series of 2,4-diamino-5-aryl-6-ethylpyrimidines embracing basic substituents in the 5-aryl ring was synthesized and evaluated for inhibitory activity against rat liver dihydrofolate reductase (DHFR). Maximal enzyme inhibition was observed for compounds bearing a benzylamino (19) or N-alkylbenzylamino substituent (29 and 30) in the 4-position of the phenyl ring and a nitro group in the 3-position, the corresponding 3-amino, 3-azido, or unsubstituted analogues proving only weakly active or inactive as DHFR inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 2 publications
0
26
0
Order By: Relevance
“…The target analogues were readily prepared from Pyrimethamine (Pyr) [26, 27]. Briefly, direct nitration of Pyr under standard condition afforded m-nitropyrimethamine (MNP) in near quantitative yield.…”
Section: Methodsmentioning
confidence: 99%
“…The target analogues were readily prepared from Pyrimethamine (Pyr) [26, 27]. Briefly, direct nitration of Pyr under standard condition afforded m-nitropyrimethamine (MNP) in near quantitative yield.…”
Section: Methodsmentioning
confidence: 99%
“…Griffin et al [124] previously reported the synthesis of lipophilic PYR derivatives as potent inhibitors of mammalian DHFR. Among a series of compounds evaluated for antitumor inhibition, the dimethyltriazenyl-substituted pyrimethamine analog 34 (Fig.…”
Section: Pyr Analogsmentioning
confidence: 99%
“…However, as the crystal structure of the diaminopyrimidine-DHFR complex was solved in 1989, [161] researchers at Abbott undertook docking studies between compound 67 and DHFR with the aim of enhancing the selectivity of their compounds. They compared the binding mode of compound 67 with DHFR and the supposed binding mode of the same compound with GHS-R1a.…”
Section: 4-diaminopyrimidinesmentioning
confidence: 99%